(untitled) (Sustainability in Debate, 2016)
Based on the fact that sustainability can be measured by means of scientifically based indicators that allow for a secure evaluation methodology and considering that the criteria for selecting this indicators are in general influenced by subjective judgements made by those who choose them, this articles seeks to propose a methodology based on the socioenvironmental perception of social actors in association with the selection of economic indicators of suatainability selected according to the Delphi methodology. Data were taken from the population and compared with the positions adopted by specialists, in order to understand the researched contexto and weed out conflicting views. Perception indicators E1, E3, E19 and E20, value-laden indicators E2, E12, E13 and atitude-based indicator E17 were selected. The conclusion is that the use of perception as related to the Delphi methodology was effective in the identification of the basic indicators for the evaluation od the economic sustainability of onshore oil fields.